A Review of the Impacts of Internal and External Dynamics on the Corporate Governance and Performance Outcomes in Pakistan - Henna; Tanveer Ahmad; Sammar Abbas; Faisal Mehmood (`, 2025)
This review article aims to analyze the impact of key governance components, such as accountability, transparency, and sustainable growth, on corporate governance. The recent studies reveal that the adoption of efficient corporate governance practices has gained importance in Pakistan due to market forces, increased investor awareness, and legislative changes. Hence, there is a need to examine the internal and external governance practices employed by Pakistani companies and their impact on stakeholder protection and business performance. For example, how do corporate governance mechanisms in Pakistan affect transparency, accountability, and organizational performance? The search initially identified 312 records, of which 20 studies met the inclusion criteria and were included in the final qualitative synthesis. Articles were selected based on relevance, publication quality, and focus on Pakistan’s corporate governance, while duplicates, non-peer-reviewed sources, and studies lacking empirical or theoretical insights were excluded. Case study papers were also selected, which have worked on the companies on the Pakistan Stock Exchange, regulatory frameworks like the Companies Act 2017 and the Securities and Exchange Commission of Pakistan (SECP), and the Code of Corporate Governance. The results imply that internal mechanisms have a favorable impact on governance procedures, including audit committees, board independence, and performance-linked managerial incentives. Such as the efficacy is limited by the inconsistent application of external processes like market discipline and regulatory enforcement. This review of the literature paper limitation is based on empirical data and secondary sources. The study concluded that both internal governance structures and external regulatory scrutiny are recommended to enhance firm performance. Future research should develop practical plans for enhancing corporate governance in Pakistan and include actionable strategies for improving the corporate governance sector-specific studies. Keywords: Corporate governance, Internal and External Dynamics, regulatory mechanisms Performance.